Canadian university students' perceptions of COVID-19 severity, susceptibility, and health behaviours during the early pandemic period - M. Mant; A. Holland; A. Prine (Elsevier, 2021)
Objectives: We surveyed university students to assess their demographic factors, perceived severity, personal susceptibility, and the adoption of health behaviours in relation to COVID-19. Study design: Ethics approval was obtained from the University of Toronto's Research Ethics Board (#39169). Responses were collected between March 20 and April 17, 2020, capturing the first month of government-mandated social distancing in Ontario, Canada. Methods: We distributed the online survey to the University of Toronto student population, yielding a total convenience sample of 592 participants. We summarised the results and conducted Mann-Whitney U and Kruskal-Wallis tests to explore relationships between demographic data and perceived severity of COVID-19. Pearson's Chi-square tests were used to explore the relationship between demographic variables and perceived susceptibility, with phi being used to explore the strength of the association. A value of p ​< ​0.05 was used to determine significance. Results: The majority of participants (60.1%) judged COVID-19 to be Very Severe; there was a significant relationship between being female and the adoption of new health behaviours. 57.4% indicated they felt susceptible to COVID-19, while 40.9% did not. Feeling susceptible was associated with studying a healthcare field or being personally affected by COVID-19. Individuals who stated they were not susceptible to COVID-19 declared mitigating factors such as new health behaviours to be a major driver in their perception. Conclusion: University students believe COVID-19 is a severe disease and have adopted new and increased health behaviours to mitigate the spread. While this study demonstrates differing health behaviour adoption rates based upon demographic factors, overall this research finds young adults supportive and accepting of government policy as a protective and susceptibility-mitigating measure.